2012
DOI: 10.1111/emr.12024
|View full text |Cite|
|
Sign up to set email alerts
|

Home ranges of introduced rats on Christmas Island: A pilot study

Abstract: Summary Understanding the spatial ecology of invasive rats (Rattus spp.) is necessary to inform management actions to reduce their impact on native flora and fauna. This study investigates home range sizes of exotic rats around seabird colonies and urban areas on Christmas Island, where rat predation is suspected to be adversely affecting fledgling success among local seabirds. It was hypothesised that rat home range sizes would be smaller in urban areas owing to more consistent food availability. Home ranges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 21 publications
7
23
0
Order By: Relevance
“…Different rat tracking methods provide distinctive information on rat space use scales. The HR 95 values from SECR modelling used as estimators for total area ranged by rats (pooled over individuals) are consistent with previous home range studies on tropical islands using radio-tracking and other live-trapping methods (Low et al 2013). Basic statistics on maximum range extent (MMDM) derived from trapping distances confirmed a habitat effect on distances moved by rats although they clearly underestimate total rat home range and could not supply useful information on true range boundaries.…”
Section: Range Scalessupporting
confidence: 77%
See 1 more Smart Citation
“…Different rat tracking methods provide distinctive information on rat space use scales. The HR 95 values from SECR modelling used as estimators for total area ranged by rats (pooled over individuals) are consistent with previous home range studies on tropical islands using radio-tracking and other live-trapping methods (Low et al 2013). Basic statistics on maximum range extent (MMDM) derived from trapping distances confirmed a habitat effect on distances moved by rats although they clearly underestimate total rat home range and could not supply useful information on true range boundaries.…”
Section: Range Scalessupporting
confidence: 77%
“…Previous studies have shown that rat home range size may vary due to a large number of factors including sex of individuals, population density, food availability and population breeding cycle (Innes & Skipworth 1983;Hooker & Innes 1995;Low, Mills, Algar, & Hamilton 2013). On tropical islands rat dynamics are primarily driven by bottom-up effects with summer high densities associated with seasonal pulses of rainfall (Harris & Macdonald 2007;Russell et al 2011).…”
Section: Space Use Dynamicsmentioning
confidence: 99%
“…For both Norway and black rats (hereafter termed "rats" when referencing both species), the home range size and shape is determined by access to feeding and harborage sites (Davis et al, 1948;Recht, 1982;Low et al, 2013) as well as access to mates (Low et al, 2013;Glass et al, 2016). These associations lead to irregularly shaped home ranges with individuals often moving along narrow pathways connecting harborage and food sources (Davis et al, 1948;Recht, 1982;Recht et al, 1983).…”
Section: Home Rangementioning
confidence: 99%
“…rats (Low et al, 2013;Oyedele et al, 2015). Beyond the value of regular access to resources, an intimate familiarity with the features of the home range may serve as a protective measure for rats.…”
Section: Home Rangementioning
confidence: 99%
“…These authors record several island reptile declines (lizards, tuatara) induced by the introduction of R. rattus, R. exulans or R. norvegicus. The blue-tailed skink (Cryptoblepharus egeriae) is assumed to have declined because of rodent predation on Christmas Island (Low et al 2013), which is also the case for the endemic Belize leaf-toed gecko (Phyllodactylus insularis) on Half Moon Caye (Meerman 1996) and the whiptail lizard (Cnemidophorus vanzoi) on St Lucia (John 1999). On Rodrigues Island, large gecko species (Phelsuma edwardnewtoni and P. gigas) were devastated after rat introductions (Vinson & Vinson 1969).…”
Section: Introductionmentioning
confidence: 99%